2016
DOI: 10.1007/s12221-016-5660-3
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic mechanical behavior of 3D integrated woven spacer composites with thickened face sheets

Abstract: 3D integrated woven spacer composites with thickened face sheets are fabricated successfully. Static compression and impact behavior are analyzed to evaluate the effect of thickened face sheets. The results show that thickened face sheet is an important influence parameter, warp compression and impact properties have been improved significantly than those of composite without thickened face sheets. Moreover, the damage and failure mechanism is significantly different. The main failure mode under flat compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…And the accuracy of the analytical model was verified by experiments and finite element analysis . The low‐velocity impact response of 3D‐integrated‐core sandwich laminates filled with and without foam, with and without additional GFRP or CFRP face sheets was investigated . Vaidya et al studied the properties of stitched cores with and without foams around the reinforcing core members.…”
Section: Innovative Foam Sandwichmentioning
confidence: 99%
See 1 more Smart Citation
“…And the accuracy of the analytical model was verified by experiments and finite element analysis . The low‐velocity impact response of 3D‐integrated‐core sandwich laminates filled with and without foam, with and without additional GFRP or CFRP face sheets was investigated . Vaidya et al studied the properties of stitched cores with and without foams around the reinforcing core members.…”
Section: Innovative Foam Sandwichmentioning
confidence: 99%
“…The weak interface between the face sheets and the core of the traditional sandwich structures is one of their major drawbacks. Several studies have been carried out to strengthen the interface bonding including integrated design of face sheets and core, stitching techniques and increasing of the bonding areas . Several technologies have been introduced for sandwich structures improving their mechanical performance and multifunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to skin, the empty core has a low shear resistivity [5] which causes the structure to perform weakly under compressive, impact, and shear loadings. In order to overcome the mentioned drawbacks and improve mechanical properties of 3DIWF composites, two useful methods were utilized by many researchers, injecting foam into the core and thickening the face sheets [10,[18][19][20][21]. Their results showed that by introducing foam into the core, shear resistivity of the core could be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flexural modulus and shear modulus increase as foam density increases. On the other hand, other studies showed that face sheet thickness is a vital parameter influencing mechanical performance of 3DIWF composites [18,20,21]. For instance, Li et al [20] investigated the effect of thickening face sheets on mechanical properties of 3DIWF composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation